PENGEMBANGAN WEBSITE SEBAGAI MEDIA PEMBELAJARAN IPAS UNTUK MENINGKATKAN PEMAHAMAN TERKAIT PEDULI LINGKUNGAN KELAS V SEKOLAH DASAR - Sherly Marlinda; Yustia Suntari; Prayuningtyas Angger Wardhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop the ALAM (Safe and Enjoyable Environment Application) website-based learning media using Google Sites for the Environmental Damage topic in the Natural and Social Sciences (IPAS) subject for fifth-grade elementary school students, to determine the feasibility of the developed media, and to examine the improvement of students' understanding of environmental awareness after using the media. This study employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The research subjects were 32 fifth-grade students at SDN Klender 03 Pagi. Data were collected through observations, interviews, questionnaires, and tests, and were analyzed using descriptive qualitative and quantitative techniques based on expert validation, student trials, and the analysis of pretest and posttest scores using the N-Gain score. The results indicated that the developed media achieved an average feasibility score of 95%, which falls into the very feasible category. Furthermore, the results of the student trials also indicated that the media was categorized as very feasible. The average pretest score increased from 67.03 to 92.03 on the posttest, with an N-Gain score of 0.75, which is classified as high. Based on these findings, the Google Sites-based ALAM learning media is considered highly feasible for use and is effective in improving students' understanding of environmental awareness in Natural and Social Sciences (IPAS) learning for fifth-grade elementary school students.